2020
DOI: 10.1021/acs.analchem.0c00093
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Coated Blade Spray for Rapid Screening and Quantitation of 105 Veterinary Drugs in Biological Tissue Samples

Abstract: Rapid and efficient determination of contaminants at trace levels in tissue samples has become an unmet need around the globe. Coated blade spray (CBS) extraction/ionization is a technology capable of performing, with a single device, enrichment of analytes present in complex matrices, as well as the direct interface and introduction of said analytes into the mass spectrometer via electrospray ionization. To facilitate the challenging rapid tissue screening, we describe for the first time the use of a very thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Since its inception, the use of CBS has been primarily focused on bioanalysis 31 . Recently, the technology was shown to be also suitable for rapid food screening and quantitation by work that has set important breakthroughs, not only in food analysis but also in microextraction technology interfaces with MS instrumentation 28,29 . For instance, Kasperkiewicz et al proposed for the first time optimization of extraction time based on signal‐to‐noise ratios instead of mere instrumental signal.…”
Section: Cbs‐msmentioning
confidence: 99%
See 4 more Smart Citations
“…Since its inception, the use of CBS has been primarily focused on bioanalysis 31 . Recently, the technology was shown to be also suitable for rapid food screening and quantitation by work that has set important breakthroughs, not only in food analysis but also in microextraction technology interfaces with MS instrumentation 28,29 . For instance, Kasperkiewicz et al proposed for the first time optimization of extraction time based on signal‐to‐noise ratios instead of mere instrumental signal.…”
Section: Cbs‐msmentioning
confidence: 99%
“…Poole et al first demonstrated the suitability of the technique for the determination of a group of pharmaceuticals in environmental water samples 32 . Subsequently, Khaled et al investigated the potential of CBS‐MS/MS technology for effective monitoring of 105 veterinary drugs in homogenized bovine meat 29 . This work achieved for the first time the of use both negative and positive ionization modes in one single run with the same CBS device.…”
Section: Cbs‐msmentioning
confidence: 99%
See 3 more Smart Citations